Usulan Desain Kemasan Pupuk Organik Padat dan Cair dalam Meningkatkan Value Added UMKM REPRO - Aulia, Arshinta Wilda; Setyaningrum, Ratih; Arsiwi, Pramudi; Andayani, Karenina Puri (Fakultas Teknik Universitas Tulang Bawang, 2025)
Micro, Small and Medium Enterprises (MSMEs) Organic Product Engineering (REPRO) is one of the MSMEs that is trying to reduce organic waste, namely by processing organic waste using BSF (Black Soldier Fly) flies. In addition to decomposing organic waste, the production results at UMKM REPRO produce derivative products that have selling value, namely solid organic fertilizer resulting from filtering used maggot feed and liquid organic fertilizer obtained from filtering fermented maggot feed. With the existence of products that have selling value, it is necessary to develop product packaging design with development efforts that are implemented to increase value added, branding, attractiveness and competitiveness in facing the modern market with good product quality, and relatively cheap product prices from the results of ideas through creative and innovative behavior. The objective of this research is to provide a packaging design proposal that can compete in the market and analyze the added value of MSMEs in the development of solid and liquid organic fertilizer product packaging. Keywords: Attraction, Design, Liquid Organic Fertilizer, Packaging, Solid Organic Fertilizer